Continuous Infusion of Ketamine in Mechanically Ventilated Patients with SARS-CoV-2 - Brian Phan; Afua Agyemang; Walter Klein; Suman B. Thapamagar (Critical Care Research and Practice)
Background. Widespread drug shortages led to higher utilization of ketamine in our intensive care unit, especially among patients with SARS-CoV-2. Objectives. To evaluate the impact of continuous infusion of ketamine on vasopressor requirements in patients with SARS-CoV-2. Method. This was a single-center, retrospective, cohort study comparing mechanically ventilated (MV), adult patients with SARS-CoV-2 receiving either propofol or ketamine for at least 72 hours. Results. 84 patients (mean age of 61-year-old, 68% male) were analyzed. 31 patients received ketamine, and 53 patients received propofol. Mean vasopressor doses were not significantly different between ketamine and propofol groups at prespecified timepoints. However, mean arterial pressures (MAP) were higher in the ketamine group at 24 h, 48 h, and 96 h postsedative initiation. The median opioid infusion requirements were 3 vs. 12.5 mg/hr (p<0.0001) for ketamine and propofol groups, respectively. Comparing to propofol, C-reactive protein (CRP) values were significantly lower in the ketamine group at 24 h (7.53 vs. 15.9 mg/dL, p=0.03), 48 h (5.23 vs. 14.1 mg/dL, p=0.0083), and 72 h (6.4 vs. 12.1 mg/dL, p=0.0085). Conclusion. In patients with SARS-CoV-2 on MV, there was no difference in the vasopressor requirement in patients receiving ketamine compared to propofol. Nevertheless, the use of ketamine was associated with higher MAP, reductions in CRP in select timepoints, and overall lower opioid requirements.